Distributions of organochlorine pesticides in sediment and aquatic biota: Benzenehexachlorides (BHCS) / Azlina Mat Saad and Fadli Fizari Abu Hassan Asari - Mat Saad, Azlina; Hassan Asari, Fadli Fizari Abu (2019)
The usage of organochlorine pesticides (OCPs), which is also known as persistent organic pollutants (POPs), is either prohibited or restricted. However, a number of studies on sediments and aquatic biotas including fish and shellfish revealed that most of the compounds for instance Benzenehexachlorides (BHCs) group are still present in the environment. Aquatic biotas can be used as bioindicator to monitor the concentrations of BHCs in the aquatic systems such as rivers and oceans. At the same time, sediments can also be used to investigate the existence of BHCs in the environment. Sediments serve as a home for benthic biota such as worms and clams, which are commonly consumed by fish and benthic feeders. OCPs are easily absorbed on suspended particulate organic matter due to their high octanol–water partition coefficient (Kow) which accumulated in bed sediments, which makes the sediments as potential contamination source.